ANALYSIS OF THE EFFECT OF METEOROLOGICAL PARAMETERS ON SEASONAL VARIATION SUSPENDED PARTICULATE MATTER (SPM) CONCENTRATION - Anjarsari, Kartika
Samarinda is a coal mining area with 70% of its concession area covering its total territory thus potentially cause an effect to air pollution related to particulate. Meteorological parameters can affect the concentration of pollutant seasonally. Therefore, an analysis was made to highlight the effect of meteorological parameters toward seasonal variation of Suspended Particulate Matter (SPM) concentration in Station Temindung, Samarinda. Data were processed using Exploratory Data Analysis (EDA) method to analyze the effect of meteorological parameters such as rainfall, wind speed and direction, and virtual temperature on the concentration of SPM seasonally. Based on data processed and analyzed, it was found that the seasonal variations in the concentration of SPM in Station Temindung, Samarinda showed low concentration on DJF and MAM season and high concentration on JJA and SON season. Rainfall was indicated significantly reduced the concentration of SPM in every season. Wind could lower the concentration of SPM on the DJF and MAM, but raising the concentration of SPM on the JJA and SON. Meanwhile, the virtual temperature was indicated to raise the concentration of SPM on SON.